Psychopharmacological treatment and fitness to work in Italian police officers: Analysis of the phenomenon and new perspectives - Silvana MASELLI; Lucilla VERGNANI; Alberto PORTIGLIATTI POMERI; Marco LUNA; Fabrizio CIPRANI (GIornale Italiano di Psicologia e Medicina del Lavoro, 2021)
Police officer is considered to be hazardous to the safety and health of their colleagues, customers, and other people, in case of substance use, abuse or dependence. In Italy, the Health Service De- partment of the State Police, employs medical officers who perform clinical care and medico-legal activity to address all the issues concerning the health and safety of police officers at workplace. Depression and poor mental health outcomes are increasingly prevalent at workplace, and are expected to increase due to an ageing workforce. Mental health-related stigma in police officers can result in social stigma, delayed treatment and poor mental outcomes. In Italy, workplace al- cohol and drug testing is compulsory by law for specific categories of workers. The recent change of an Italian Regulation (article 48, DPR n. 782/85), will allow police officers who are affected by mental health problems and/or are under treatment with psychotropic drugs, to continue to work with some restrictions, and enjoy supportive psychotherapy. This will improve their therapeutic compliance and integration at workplace.